2014
DOI: 10.1016/j.meatsci.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile and cholesterol content of beef at retail of Piemontese, Limousin and Friesian breeds

Abstract: Samples of longissimus thoracis muscle of young bulls belonging to Piemontese (n=10), Limousin (n=11) and Friesian (n=10) breeds were analysed in order to study the chemical composition, fatty acids and cholesterol content of beef purchased at retail. The breeds and their differences in intramuscular fat content strongly influenced the fatty acids profile. The Piemontese animals displayed the lowest intramuscular fat and SFA content, while Friesian animals showed the highest intramuscular fat, SFA and MUFA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
47
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 25 publications
(46 reference statements)
12
47
6
1
Order By: Relevance
“…Moreover, SFA and MUFA were positively correlated, whereas PUFA was negatively correlated with the intramuscular fat content. These results are in close agreement with the findings of Brugiapaglia et al (2014) in Bos taurus breeds, and are caused by the decrease in the phospholipids/neutral lipids ratio that arises from the increase in the intramuscular fat, as shown by Itoh et al (1999) in steers of Bos taurus breeds. Indeed, C16:0, C18:1n-9c and total SFA are present mainly in the neutral fraction, whereas C18:2n-6c and total PUFA are present mainly in the phospholipids fraction.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, SFA and MUFA were positively correlated, whereas PUFA was negatively correlated with the intramuscular fat content. These results are in close agreement with the findings of Brugiapaglia et al (2014) in Bos taurus breeds, and are caused by the decrease in the phospholipids/neutral lipids ratio that arises from the increase in the intramuscular fat, as shown by Itoh et al (1999) in steers of Bos taurus breeds. Indeed, C16:0, C18:1n-9c and total SFA are present mainly in the neutral fraction, whereas C18:2n-6c and total PUFA are present mainly in the phospholipids fraction.…”
Section: Resultssupporting
confidence: 90%
“…However, high lys/met in late castrated animals showed higher moisture content than in early castrated animals (P = 0.017). Nevertheless, moisture percentages in all treatments were lower (from 72.2% to 73.7%) than those found by Brugiapaglia et al (2014) in entire Friesian males. This was probably due to the higher fatness in the animals under study, since fluctuations in moisture percentage are often attributed to variations in lipid percentage (Rotta et al, 2009).…”
contrasting
confidence: 63%
“…This failure did not occur in our experiment and hence, our higher results for intramuscular lipids. Nevertheless, castration positively increased lipid composition in comparison with similar entire animals fed similar diets (Partida et al, 2007b) and even the leanest animals showed higher intramuscular fat compared with other entire Friesian slaughtered at a heavier weight (Brugiapaglia et al, 2014). In general, ash percentage was higher (P = 0.014) for the high dietary protein and high lys/met treatments although ash percentage is not influenced by age of castration or feeding management (Padre et al, 2007).…”
mentioning
confidence: 81%
“…Palmitic acid C16:0 constituted the second major fatty acid detected [20][21][22][23][24][25][26][27][28] , followed by stearic acid C18:0, 10-19 , palmitoleic acid C16:1 cis, [2][3][4][5] , myristic acid C14:0, 2-4 and linoleic acid C18:2 n6, 2-10 . In the storage fat, the saturated fatty acids SFA were present in significantly p 0.05 greater amounts in calf and young bull 46.76 and 47.62…”
Section: Fatty Acid Composition Of By-productsmentioning
confidence: 99%
“…Besides, CA sample had the highest concentration in the C18:2 n6. According to De Smet et al 22 and Brugiapaglia et al 23 about the investigation on the fatty acid profile of Longissimus thoracis muscle from different Belgian and Italian young bulls, SFA was the predominant class followed by MUFA and PUFA. For SFA class our results range 23 .…”
Section: Fatty Acid Composition Of By-productsmentioning
confidence: 99%